Representation of popular Korean culture (K-Pop) Industrial Identity through a virtual ethnographic approach - Rosseta Septia Menawati; Addin Kurnia Putri (Penerbit Universiti Kebangsaan Malaysia, 2023)
The popularity of Korean pop (K-Pop) culture can be seen through the growth of a massive fan base without age restrictions, and is currently the largest in the music and entertainment industry. K-Pop fans who occupy a fandom are known as K-Popers. This present study explains the representation of identity in essence, as according to Hall - is related to the use of language, and represents a “blurring” of meaning by a cultural industry aiming for commercialisation. The result of this research shows the process of blurring meaning by talent agencies that produce K-Pop idols as the main product that represent them by carrying important values that will be adapted and consumed by fans with strong loyalty and emotional connection. The agency is a cultural business industry that sells its “products” such as K-Pop idols that they have introduced to fans, and refers to their “existence” that is consumed by fans. This study used a virtual ethnographic approach with data collection techniques through participant observation and interviews. Each of these main products has its own unique concept as every fan will feel special and exclusive as K-Pop music is a sense of "individuality" developed by the K-Pop culture and industry. Based on the results of observations on Instagram, we can find various types of fans to describe how they adapt the meaning that is sold by the agency through the products they sell.